Cognitive Approach to the Use of Multimedia in Maharoh Kalam Learning - Triwibowo, Muhammad; Taufiqurrochman, Raden; Hasaniyah, Nur (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Mastery of speaking skills in learning Arabic often faces challenges related to student engagement and the effectiveness of traditional teaching methods. Conventional teaching methods are usually considered less attractive and unable to meet the learning needs of students effectively. This study aims to explore the use of multimedia based on a cognitive approach to improving students' speaking skills in the Special Arabic Language Learning Program (PKPBA) UIN Malang. Qualitative research methods were used, involving in-depth observations and interviews with students and faculty to collect data on the experience and impact of multimedia use. The results showed that multimedia designed with a cognitive approach significantly improved students' speaking skills, increased motivation, and enriched the learning experience. These findings make an important contribution to cognitive theory by demonstrating the practical application of multimedia in language learning, as well as providing guidance for educators in designing more effective learning materials. This research also emphasizes the need for inclusive technology development, attention to ethics, and the protection of users' data. Keywords: Speaking Skills, Multimedia, Cognitive